Exploring Measurement Comparability of Accommodated Math Tests for Students With Emotional Impairments. (1st October 2020) - Witmer, Sara E.; Roschmann, Sarina
Abstract: It is critical to examine whether test accommodations function as intended in removing construct-irrelevant variance. The measurement comparability of a math test for students with emotional impairments and those without disabilities was examined. Results indicated the presence of limited differential item functioning (DIF) regardless of accommodation status.